Computational propaganda in Poland: false amplifiers and the digital public sphere - Gorwa, R (Computational Propaganda Research Project, 2017)
This report provides the first overview of political bots, fake accounts, and other false amplifiers in Poland. Based on extensive interviews with political campaign managers, journalists, activists, employees of social media marketing firms, and civil society groups, the report outlines the emergence of Polish digital politics, covering the energetic and hyper-partisan “troll wars”, the interaction of hate speech with modern platform algorithms, and the recent effects of “fake news” and various sources of apparent Russian disinformation. The report then explores the production and management of artificial identities on Facebook, Twitter, and other social networks— an industry confirmed to be active in Poland—and assesses how they can be deployed for both political and commercial purposes. The quantitative portion of the report features an analysis of Polish Twitter data, and demonstrates that a very small number of suspected bot accounts are responsible for a disproportionally large proportion of activity on the sampled political hashtags. Furthermore, within this dataset, there appear to be twice as many suspected right-wing bot accounts as there are left-wing accounts. These right-wing accounts are far more prolific than their left-wing counterparts, with a tiny number of highly active right-wing accounts generating more than 20% of the total volume of political Twitter activity collected over a three-week period. Overall, the report provides evidence for a rich array of digital tools that are increasingly being used by various actors to exert influence over Polish politics and public life.